Cyclist Endofibrosis (Exercise-Induced Arterial Endofibrosis) Treated by Drug-Coated Balloon Angioplasty - Ahmed S. Zugail; Hossam I. Shaabi; Slimane Idir; Jean-Pierre Becquemin (Case Reports in Vascular Medicine)
Exercise-induced arterial endofibrosis is an uncommon entity that is most frequently identified in high-performance athletes, especially cyclists. We present this disease in a male professional cyclist of 22 years of age. The course of his condition, clinical manifestations, modalities of investigation, and a nonprecedent treatment plan are demonstrated.